Kewenangan Dinas Pendapatan Daerah dalam Pengelolaan Perparkiran Berdasarkan Perda No. 05 Tahun 2004 tentang Pajak Parkir Pengaruhnya Terhadap Peningkatan Pendapatan Asli Daerah (PAD) Pemerintah Kota Bandung - Erga Yuhandra (Universitas Kuningan, 2015)
As the main source of local revenue, tax has a very atrategic role for the continuity of development today. Therefore, tax should be managed well and properly. Although problem of general parking has been discussed repetedly, there is no obvius solution to the this problem. The problem of existence of parking on-street generally located in the center of a crowded placa accours because many owners of shopping centre do not provide parking area for vistors. The objective of the research is to know and reviewthe authority of Dispenda in the parking management, the tax management of parking tax by Dispenda and its influence to the increace of the regional income, and the obstacles found in the parking management. The research used by the wraiter in the paper is descriptive analysis, that is illustrating the data concerning a matter that is in progress at a certain place and at a certain time and then it is analyzed. The method is juridical normative method, that is the methode using source of secondary data date consists of legal rule ordered hierarchically: 1945 Constitution, laws, government regulation, and other rule under the law. Secondary legal material is legal material obtained from taxs books, foreign journals, opinions of scholars, legal case. Tertiary legal material is legal material that provides instructions or explanations to the primery or secondary legal materials, such as legal dictionary and encyclopedia. The result of the research shows that Dispenda does not have the authority to determine the amount of parking tariff managed by the privat sector. The management of parking tax is in accordance with applied regulations and it is effective. The obstacles found in parking management are the limitide parking area, the messy parking, and the parking arrangement that is not professional. Key word : Authority, Management, Tax parks